Acute lysyl oxidase inhibition alters microvascular function in normotensive but not hypertensive men and women - Craighead, Daniel H. (Am J Physiol Heart Circ Physiol, 2018)
The lysyl oxidase (LOX) family of enzymes regulates collagen cross-linking. LOX is upregulated in hypertension, increasing vascular stiffness. In vivo human research is sparse, as long-term LOX inhibition in animals causes vascular instability. Our aim was to evaluate the effects of LOX inhibition on cutaneous microvascular function to determine whether LOX function was upregulated in hypertensive humans. Four intradermal microdialysis fibers were placed in the forearm of 10 young [age: 24 ± 1 yr, mean arterial pressure (MAP): 87 ± 2 mmHg], 10 normotensive (age: 50 ± 2 yr, MAP: 84 ± 1 mmHg), and 10 hypertensive (age: 53 ± 2 yr, MAP: 112 ± 2 mmHg) subjects. Two sites were perfused with 10 mM β-aminopropionitrile (BAPN) to inhibit LOX. The remaining two sites were perfused with lactated Ringer solution (control). A norepinephrine dose response (10(−12)−10(−2) M) was performed to examine receptor-mediated vasoconstrictor function. A sodium nitroprusside dose response (10(−8)−10(−1.3) M) was performed to examine vascular smooth muscle vasodilator function. Red blood cell flux was measured via laser-Doppler flowmetry and normalized to cutaneous vascular conductance (flux/MAP). LogEC(50) values were calculated to determine changes in vasosensitivity. Skin tissue samples were analyzed for both extracellular matrix-bound and soluble LOX. LOX inhibition augmented vasoconstrictor sensitivity in young (control: −6.0 and BAPN: −7.1, P = 0.03) and normotensive (control: −4.8 and BAPN: −7.0, P = 0.01) but not hypertensive (control: −6.0 and BAPN: −6.1, P = 0.79) men and women. Relative to young subjects, extracellular matrix-bound LOX expression was higher in hypertensive subjects (young: 100 ± 8 and hypertensive: 162 ± 8, P = 0.002). These results suggest that upregulated LOX may contribute to the vascular stiffness and microvascular dysfunction characteristic in hypertension. NEW & NOTEWORTHY Matrix-bound lysyl oxidase (LOX) and LOX-like 2 expression are upregulated in the microvasculature of hypertensive men and women. Microvascular responsiveness to exogenous stimuli is altered with localized LOX inhibition in healthy men and women but not hypertensive adults. The LOX family differentially affects microvascular function in hypertensive and normotensive men and women.